How to Develop Caricature Media Based on Al-Qur'an Verses in Thematic Learning in Elementary School - Megawati Megawati; Mardi Takwim; Firman Firman (IAIN Manado, 2022)
How to develop caricature media based on Al-Qur'an verses in thematic learning in elementary school. Developing creative and interesting learning media for elementary school students is important and must receive attention. This study aims to develop a caricature media that is integrated with the verses of the Qur'an. The type of research used is the Research and Development (R&D) ADDIE model, which consists of five stages, namely Analyze, Design, Development, Implementation, and Evaluation. This study involved three validators, 17 fourth-grade students at SDN 114 Pincara, and one teacher. The instruments used are teacher interview guidelines and student questionnaires. The study results reveal the need for interesting and not boring learning media. This research produces a product in the form of a caricature with a high validity level. The validation results from material and language experts obtained a percentage of 90% with a very valid category. In comparison, the validation results from learning media design experts obtained a percentage of 82.5% with a very valid category, while the results of validation by the homeroom teacher IV obtained a percentage of 95% with a very valid category.